Liberdade de expressão e direito penal : uma releitura dos crimes contra a honra harmonizada à Constituição (Doutrina da actual malice, verdade e justificação) - Silva, Daniany Souza da (2012)
The present work aims to conform the Brazilian criminal law, especially the offenses against the honor, to a contemporary understanding of freedom of expression. First of all, it was established how serious is the threat posed by these laws to this fundamental freedom, conclusion which inspired its study in the American constitutional system, where the First Amendment has a large "breathing space". Still, by analyzing the First Amendment doctrines, the study of criminal defamation, particularly at state level, and by understanding the actual malice standard, it was discovered that the truth and the right to critique are protected by freedom of expression and awarded by the exchange of ideas in a democracy. Finally, it was found that truth and justification form the core of this fundamental right in Brazil on grounds similar to American law, ensuring the debate in society, protecting it from possible criminal actions filed by public officials, public figures or even individuals involved in matters of public interest which have as their goal to deter criticism and censor the truth